Unilateral Blindness in a Patient Following Root Canal Treatment - Shushtarian, Seyed Mohammad Masoud; Pour Mazar , Reza (Journal of Ophthalmic and Optometric Sciences, 2023)
Root canal treatment is a dental procedure that relieves pain caused by an infected or abscessed tooth. It is one of the safest and most successful dental procedures. However, the patient may face unexpected complications during or after the procedure in certain rare conditions. The ocular complication is among these conditions. In the present work, we present a case of a 45-year-old male patient who suffered from pain and unilateral blindness after root canal treatment. He was referred to Basir eye clinic for a visual evoked potential test as part of his eye examination to reach an accurate diagnosis.